Toward a critique of guilt perspectives from law and the humanities - Anderson, Matthew; Sarat, Austin (Bingley, U.K. : Emerald, 2005)
This special volume of "Studies in Law, Politics, and Society" takes up a subject of an enormous import for law and legal scholarship, Guilt. At the center of our belief in law is the hope and expectation that law can differentiate the guilty from the innocent. But as the articles in this volume show law's relationship to guilt is more complex and vexed than that. Law constitutes us as guilty subjects and law itself is a guilty subject. The articles in this volume explore law's guilt about literature, various domains in which bodies of guilt appear, and historical perspectives on the subject of guilt. Taken together they exemplify the way interdisciplinary scholarship opens up new questions and new avenues of inquiry about the social and cultural life of law.
Introduction : guilt and utopia / Matthew Anderson -- Law's guilt about literature / Jane B. Baron -- Guilty professions : specters of sameness in Camus's The fall / Ravit Reichman -- The injustice of intersex : feminist science studies and the writing of a wrong / Iain Morland -- The cow and the plow : animal suffering, human guilt, and the crime of cruelty / Susan J. Pearson -- "Not a story to pass on" : sexual violence and ethical act in Toni Morrison's Beloved / Sara Murphy -- Was Cain innocent? : the early rabbis interpret guilt / Chaya Halberstam -- Eternal remorse / Linda Ross Meyer.
Keywords: Law -- General; Social Science -- Sociology -- General; Jurisprudence & general issues; Sociology & anthropology; Guilt (Law); Guilt -- Religious aspects; Guilt; Guilt in literature